2022
DOI: 10.1177/21650799221117273
|View full text |Cite
|
Sign up to set email alerts
|

Fluid Intake and Hydration Status Among North Carolina Farmworkers: A Mixed Methods Study

Abstract: Background: Agricultural workers are disproportionately at risk for heat-related morbidity and mortality. The purpose of this study was to explore how sociocultural and occupational factors, and environmental heat stress influenced fluid intake and hydration status among Latino farmworkers working in eastern North Carolina. Methods: A community-informed, mixed methods research study was conducted in partnership with staff at a federally qualified health center. In summer 2020, we recruited Latino farmworkers a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…And that these farmworkers spent the majority of their shift working in temperatures above the recommended limits for workplace heat exposure. 39 Another farmworker study reported that dehydration was related to decreased kidney function, kidney function significantly decreased between pre-and postharvest, and that pesticide exposure needs to be considered along with dehydration status and heat stress. 40 Relationships between field sanitation, size of employer, type of employer, and occupational exposures collected using walk-through surveys also warrants additional consideration.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…And that these farmworkers spent the majority of their shift working in temperatures above the recommended limits for workplace heat exposure. 39 Another farmworker study reported that dehydration was related to decreased kidney function, kidney function significantly decreased between pre-and postharvest, and that pesticide exposure needs to be considered along with dehydration status and heat stress. 40 Relationships between field sanitation, size of employer, type of employer, and occupational exposures collected using walk-through surveys also warrants additional consideration.…”
Section: Resultsmentioning
confidence: 99%
“…Dehydration may result in mental and physical fatigue, less attention and focus, or balance‐related problems, which could predispose the crop workers to illness or injuries. Mizelle et al 39 reported that hydration status, measured by urine specimens, among North Carolina farmworkers significantly deteriorated to the extent they were dehydrated or severely dehydrated by the end of a workday. And that these farmworkers spent the majority of their shift working in temperatures above the recommended limits for workplace heat exposure 39 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation